Semiconductor sector: Trends issues and challenges - Nataraj, Geethanjali and Joshi, Nikhil (IIPA Digest)
Developing semiconductors within the country is essential for the Indian government's goal of establishing a domestic electronics supply chain and decreasing reliance on foreign countries, particularly China, which continues to be a leading destination for such manufacturing despite its own problems. India is currently facing a critical moment to enter the field of electronics manufacturing, as semiconductor chips play a crucial role in all electronic devices. With more companies seeking to diversify their manufacturing, India has the chance to position itself as a dependable alternative to existing manufacturing countries. From 2017 to 2022, the semiconductor manufacturing sales value of India experienced a Compound Annual Growth Rate (CAGR) of nearly 11%. According to a report from Deloitte, the market is projected to reach a value of $55 billion by 2026, growing from $27 Billion in 2022 at a 20% CAGR. The report highlights that three industries, namely smartphones and wearables, automotive components, and computing and data storage, are expected to drive over 60% of the market growth. Following the Government$1 (Bs push under the India Semiconductor Mission, the country is said to manufacture its first Chips in December 2024, with 4-5 semiconductor facilities expected to be built by mid-2024.- Reproduced s
Keywords: Semiconductors